2021
DOI: 10.3390/ijerph18168706
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study to Assess Knowledge of COVID-19 among Undergraduate Students in North-Central Ecuador

Abstract: Adherence to preventive measures is influenced by people’s knowledge, attitudes and practices towards a disease; therefore, assessing knowledge of COVID-19 is critical in the overall effort to contain the outbreak. This cross-sectional study was conducted among undergraduates (n = 3621) of different programs and different levels of education associated with universities in north-central Ecuador. The form consisted of 32 questions covering demographics, symptoms, detection, treatment, transmission, prevention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
6
0
3
Order By: Relevance
“…Furthermore, the present outcomes demonstrate that students enrolled in programs related to applied sciences scored higher than their colleagues affiliated to social sciences, which has been hitherto described [ 20 , 22 ]. Previous studies reporting knowledge of genetics and COVID-19 have shown that students not associated with applied sciences curricula have difficulties when enquired about such matters [ 29 , 30 ]. On the other hand, no differences were found regarding sex and age range, implying that older students are no more knowledgeable than their younger counterparts, as shown before [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the present outcomes demonstrate that students enrolled in programs related to applied sciences scored higher than their colleagues affiliated to social sciences, which has been hitherto described [ 20 , 22 ]. Previous studies reporting knowledge of genetics and COVID-19 have shown that students not associated with applied sciences curricula have difficulties when enquired about such matters [ 29 , 30 ]. On the other hand, no differences were found regarding sex and age range, implying that older students are no more knowledgeable than their younger counterparts, as shown before [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information about antibiotic prescription and use does not seem sufficiently available or discernible to students, especially to those not familiar with scientific literature. It has been suggested that programs providing basic information about genetics or infectious diseases should be implemented as required credit courses, mainly for undergraduates associated with “social” curricula [ 30 ]. Undoubtedly, including antibiotic data in such courses will contribute to the promotion of protective health measures aimed at reducing their misuse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As social determinants of health measure, high social risk can increase the risk of SARS-CoV-2 infection. In Ecuador, a study showed that high levels of education were related to more virus acknowledgment [ 22 ]. However, they were less assertive about the virus’s characteristics and used empirical and unproven treatments.…”
Section: Discussionmentioning
confidence: 99%